A Review paper on Leadership models in Education - Munendra Kumar (AG Volumes, 2022)
According to this research, numerous educational leadership models are investigated in depth, as well as their significance, the most renowned academics working on every model. Educational leadership paradigms that have been researched extensively include distributed leadership, teaching, teacher leadership, and also transformational leadership. According to the study, researchers are increasingly focusing on the impact of leaders on organizational behavior and student accomplishment. The significance of leaders in leadership and management in education sectors during 21st century is presented well.